On Analytical Solution of Time-Fractional Type Model of the Fisherâ€™s Equation - Huseen, Shaheed N. (Iraqi Journal of Science, 2020)
In this paper, the time-fractional Fisherâ€™s equation (TFFE) is considered to exam the analytical solution using the Laplace q-Homotopy analysis method (Lq-HAM)â€. The Lq-HAM is a combined form of q-homotopy analysis method (q-HAM) and Laplace transform. The aim of utilizing the Laplace transform is to outdo the shortage that is mainly caused by unfulfilled conditions in the other analytical methods. The results show that the analytical solution converges very rapidly to the exact solution.